2022
DOI: 10.3390/ijms23042038
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible Gas Plasma Treatment Affects Secretion Profiles but Not Osteogenic Differentiation in Patient-Derived Mesenchymal Stromal Cells

Abstract: Cold physical plasma (CPP), a partially ionized gas that simultaneously generates reactive oxygen and nitrogen species, is suggested to provide advantages in regenerative medicine. Intraoperative CPP therapy targeting pathologies related to diminished bone quality could be promising in orthopedic surgery. Assessment of a clinically approved plasma jet regarding cellular effects on primary bone marrow mesenchymal stromal cells (hBM-MSCs) from relevant arthroplasty patient cohorts is needed to establish CPP-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…7a-e). Surprisingly, the fact that increasing the surface roughness would enhance cell attachment, spreading, proliferation, and differentiation could be violated, depending on the material, scaffold, plasma treatment type, and cells used 84 .…”
Section: Osteogenic Differentiation Alkaline Phosphatase (Alp) Enzyme...mentioning
confidence: 99%
“…7a-e). Surprisingly, the fact that increasing the surface roughness would enhance cell attachment, spreading, proliferation, and differentiation could be violated, depending on the material, scaffold, plasma treatment type, and cells used 84 .…”
Section: Osteogenic Differentiation Alkaline Phosphatase (Alp) Enzyme...mentioning
confidence: 99%
“…Further, the results confirmed that the apically facing sites of implant threads could be sufficiently reached by the WaterJet but not by cotton gauze. This might be the main reason for the underperformance of the latter since gauze treatment’s efficacy is irregular, as previously shown by Ichioka and colleagues on Streptococcus gordonii -covered titanium discs [ 69 ]. In contrast to our previous study [ 58 ], we detected surface alteration on implants treated with the WaterJet application.…”
Section: Discussionmentioning
confidence: 99%
“…The collected bone marrow was weighed in a Petri dish. BM-MNCs were isolated via density gradient centrifugation as previously described [ 22 , 28 ]. Isolated BM-MNCs were seeded on cell culture flasks with a cell density of 5 × 10 5 /cm 2 and cultured at 37 °C, 95% humidity and 5% CO 2 atmosphere.…”
Section: Methodsmentioning
confidence: 99%